ЛІКУВАННЯ КІСТ СЕЛЕЗІНКИ У ДІТЕЙ - Кузик, А. С.; Притула, В. П.; Лукавецький, І. В.; Могиляк, О. І.; Романишин, Б. С.; Синюта, А. В.; Халак, С. М.; Лешневський, О. Б. (Українські медичні вісті, 2023)
ЛІКУВАННЯ КІСТ СЕЛЕЗІНКИ У ДІТЕЙ